First-in-human cases and preclinical experience of a novel ICE catheter - Liu, Guangan; Wu, Jingjing; Fang, Fang; Zhao, Weipeng; Sun, Minmin; Zhang, Jihong; Liu, Simeng; Wang, Mimi; Liu, Feng (Frontiers in Cardiovascular Medicine, 2024)
Introduction The primary objective of our study was to evaluate the first use of a novel intracardiac echocardiography (ICE) catheter in human subjects. This study aimed to assess its practicality, image clarity, and guidance role during electrophysiology procedures. Methods Two patients underwent procedures using the novel ICE catheter. Post-procedure evaluations were conducted by four operators, who assessed the imaging quality and overall performance of the catheter. Anatomical and blood test results were also analyzed to determine the safety and impact on internal cardiac structures. Results Both patients were discharged one day after the procedure without any complications. The novel ICE catheter provided comparable imaging quality to existing commercial catheters. The catheter's advanced design allowed for detailed imaging at short distances, essential for accurate diagnosis and treatment planning. Moreover, it successfully navigated complex anatomical structures like the atrial septum and left atrial appendage. Discussion These preliminary studies indicate that the novel ICE catheter achieves a level of safety and effectiveness comparable to previously available commercial catheters. The findings highlight its potential to meet current clinical needs, particularly in sophisticated anatomic interventions. Despite the prolonged thrombin time after anticoagulant administration, both types of ICE catheters were non-damaging to cardiac structures during routine operations. The study underscores the importance of using trans-septal large inner diameter sheaths to minimize complications when advancing the catheter into the left atrium.